2014
DOI: 10.1007/s40473-014-0009-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation (tDCS): Modulation of Executive Function in Health and Disease

Abstract: Transcranial direct current stimulation (tDCS) is a noninvasive method of neuromodulation used in human basic and clinical neuroscience. In this article we review its use in the cognitive neurosciences to study executive function, and current preliminary explorations of its therapeutic value as a cognitive enhancer for patients with compromised dysexecutive symptoms. We discuss published studies analyzing their methodology and results. A number of experiments describe improvement in experimental measures of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 91 publications
0
23
0
Order By: Relevance
“…Another will be to determine how the neural mechanisms underlying these functional aspects of effort relate to those giving rise to the subjective experience of effort (Kurzban et al 2013). On these and other fronts, the project of translating effort into neural terms may benefit from the application of causal neural techniques available for human research, such as transcranial magnetic stimulation and transcranial direct current stimulation, approaches that are becoming more widely utilized in studies of cognitive control and motivation (Reinhart & Woodman 2014, Sarkis et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Another will be to determine how the neural mechanisms underlying these functional aspects of effort relate to those giving rise to the subjective experience of effort (Kurzban et al 2013). On these and other fronts, the project of translating effort into neural terms may benefit from the application of causal neural techniques available for human research, such as transcranial magnetic stimulation and transcranial direct current stimulation, approaches that are becoming more widely utilized in studies of cognitive control and motivation (Reinhart & Woodman 2014, Sarkis et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…30-60 min). Consequently, typical wash-out times in cross-over studies range from 1 -7 days (for reviews see (Sarkis, Kaur, & Camprodon, 2014;Stagg & Nitsche, 2011). While HD-tDCS effects on motor evoked potentials may be stronger and slightly delayed compared with conventional tDCS (Kuo et al 2013), no significant neurophysiological effects were found beyond 120 min after the end of the stimulation for HD-tDCS as well.…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%
“…30--60 min). Consequently, typical wash--out times in cross--over studies range from 1 --7 days (for reviews see Sarkis, Kaur, & Camprodon, 2014;Stagg & Nitsche, 2011). While HD--tDCS effects on motor evoked potentials may be stronger and slightly delayed compared with conventional tDCS (Kuo et al 2013), no significant neurophysiological effects were found beyond 120 min after the end of the stimulation for HD--tDCS as well.…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%